Management of spinal cord injury after traumatic spine fractures in a middle-aged welder - Xiahong Li,; Xue Wang,; Song Han,; Xiuquan Shi, (Indian Journal of Case Reports, 2021)
Traumatic spine fractures associated with injuries are uncommon but extremely severe that are known to cause significant long-term disability and socioeconomic burden. Therefore, the management after an injury is extremely crucial. We report a case of lumbar spine fracture complicated with cauda equina nerve injury. The patient had 2 years’ history of hypertension and type2 diabetes. American Spinal Injury Association (ASIA) impairment scale was Grade A. Surgeon performed posterior incision for reduction and decompression and spinal fusion with pedicle screw instrumentation at the L2–L3 level. Due to poor control of blood sugar and decreased resistance after the injury, post-operative incision healing was poor and infection occurred (Staphylococcus aureus). After debridement, drainage, and anti-infection treatment, the incision gradually healed. There was no neurological recovery on the saddle area and lower limbs even after 1 year.